2022
DOI: 10.1111/jam.15564
|View full text |Cite
|
Sign up to set email alerts
|

Priming with biocides: A pathway to antibiotic resistance?

Abstract: Aims To investigate the priming effects of sub‐inhibitory concentrations of biocides on antibiotic resistance in bacteria. Methods and results Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus were exposed to sub‐inhibitory concentrations of biocides via a gradient plate method. Minimum inhibitory concentration (MIC) and antibiotic susceptibility were determined, and efflux pump inhibitors (thioridazine and chlorpromazine) were used to investigate antibiotic resistance mechanism(s). Escherichi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 88 publications
2
5
0
Order By: Relevance
“…The diversity of bacterial protection mechanisms might be one possible explanation for the weak correlations we observed. Further, it has been shown that prolonged bacterial exposure to low biocide concentrations may result in AMR development, which is not accompanied by a stable decrease in biocide susceptibility [64,65]. Because this pathway to antimicrobial resistance induced by biocides is unrelated to changes in biocide MICs, it cannot be detected with the approach of our study.…”
Section: Discussionmentioning
confidence: 74%
“…The diversity of bacterial protection mechanisms might be one possible explanation for the weak correlations we observed. Further, it has been shown that prolonged bacterial exposure to low biocide concentrations may result in AMR development, which is not accompanied by a stable decrease in biocide susceptibility [64,65]. Because this pathway to antimicrobial resistance induced by biocides is unrelated to changes in biocide MICs, it cannot be detected with the approach of our study.…”
Section: Discussionmentioning
confidence: 74%
“…Another important aspect is that antibiotics in dermatology are often used for prolonged courses, with significant potential for microbiome alteration and antibiotic‐related adverse effects 1,9,10 . Biocidal substances frequently used for the decolonization of human skin increasingly encounter the development of resistant bacteria, sometimes accompanied by cross‐resistance to antibiotics 6,59 . Clones of Escherichia coli were recently detected, which were even less sensitive to povidone‐iodine.…”
Section: Discussionmentioning
confidence: 99%
“…1,9,10 Biocidal substances frequently used for the decolonization of human skin increasingly encounter the development of resistant bacteria, sometimes accompanied by cross-resistance to antibiotics. 6,59 Clones of Escherichia coli were recently detected, which were even less sensitive to povidone-iodine. These clones additionally showed crossresistance with different antibiotics.…”
Section: F I G U R Ementioning
confidence: 99%
“…The recommended dose in adults is 50 mg to 100 mg three times daily, increasing based upon effect and tolerance to a maximum of 800 mg daily [ 34 ]. Despite its side effects, thioridazine has been the recent focus of repurposing as an anticancer drug [ 15 , 16 , 35 , 36 ], as an antibacterial [ 17 – 20 , 37 , 38 ] and as an antiviral [ 39 ].…”
Section: Discussionmentioning
confidence: 99%